The effect of ketamine on the immature granulocyte and C-reactive protein concentration in rat models of sepsis - Aswoco Andyk Asmoro; Isngadi Isngadi; Ristiawan Muji Laksono; Ibnu Firdiansayah; Agus Supriyanto (Bali Journal of Anesthesiology, 2019)
Background: Sepsis directly affects the immune system, leads tissue damage, and forms system organ dysfunction. The immunological biomarker of sepsis has a possibility to become an immunotherapy target of sepsis. This study was conducted to determine the effect of ketamine on the number of immature granulocyte and C-reactive protein (CRP) concentration in rat models of sepsis. Materials and Methods: This study used thirty white mice (Rattus norvegicus) divided into six treatment groups. The negative control group received nothing, and the positive control (sepsis) group was fecal-induced peritonitis (FIP) by fecal administration (i. p). The treatment groups (A, B, C, and D) treat with ketamine 5 mg/kg body weight (i. p.) right after FIP, 3 h after FIP, 5 h after FIP, and intermittent every 2 h. The peripheral mononuclear blood cell was isolated 6 h after FIP. The immature granulocytes counted using a hematology analyzer while CRP concentration analyzed using kit enzyme-linked immunosorbent assay. Data were analyzed statistically using the one-way ANOVA test using SPSS version 20 software (P < 0.05). Results: Sepsis induction with FIP increases the number of immature granulocytes in animal models from 0.48% to 9.12% (P < 0.05) but did not affect CRP concentration (P > 0.05). The ketamine administration significantly decreases the immature granulocytes in Groups C (1.04%) and D (1.58%). Ketamine administration did not have a significant effect on CRP concentration. Conclusion: The ketamine administration at 5 h after FIP and intermittently every 2 h can be an alternative to be sepsis immunotherapy with immature granulocyte as the potential target.